I'm Number One - Michael Rosen
'I'm A-One. I'm big A-One. Let me tell you, A-One rules'. But without other people to wind his key, A-One, big A-One, is a useless, no-good no-one! Luckily, Maddy and Sally and Sid find the perfect way to show the bully how much he really needs them.